PERILAKU PEMBELIAN IMPULSIF PRODUK FASHION DI E-COMMERCE SHOPEE: PERAN GAYA HIDUP BELANJA, MOTIVASI BELANJA HEDONIS, DAN PROMOSI PENJUALAN - Afra Arih Sausan; Sri Rejeki Ekasasi (Bajang Institute, 2026)
This Study to determine the effect of shopping lifestyle, hedonic shopping motivation and sales promotion on Impulse buying products fashion in e-commerce Shopee. The population of this study were consumers who had made unplanned purchases of fashion products on Shopee e-commerce and were aged 18-39 years. Sampling was carried out using purposive sampling technique. This study uses primary data obtained based on the distribution of questionnaires to 100 respondents via Google Form. The data analysis technique used is multiple linear analysis. The results of this study indicate that Shopping lifestyle has a positive and significant effect on Impulse buying of fashion products on Shopee e-commerce, hedonic shopping motivation has a positive and significant effect on Impulse buying of fashion products on Shopee e-commerce, sales promotion has a positive but not significant effect on Impulse buying of fashion products on Shopee e-commerce